MODEL ALLOMETRIK BIOMASSA DI ATAS PERMUKAAN TANAH PADA SISTEM AGROFORESTRI MAMAR DI DESA OEBOLA DALAM - Yudhistira Ora; . Adrin (Politeknik Pertanian Negeri Kupang, 2018)
Biomass estimation plays an important role in a climate change mitigation project in the forestry sector. Biomass estimation could be calculated using allometric equation. The aim of this research was to develop an allometric equation for mamar system, a traditional agroforestry system inVillage of Oebola Dalam, Sub District of Fatuleu, District of Kupang. The data was collected using a random sampling with a total of 15 plots developed and each plot was 20 x 20 m in size. The results of the research show that number of trees in the system is 1,350 trees per ha and is dominated by pinang (Arecha catechu). The allometric model developed is Y = 0,32 X 0,65. Thismodel can be used for the same systems in other areas.